INFLUENCE OF INSTAGRAM ON LIFESTYLE OF STUDENTS - Imam Subiyanto (Fox Justi : Jurnal Ilmu Hukum, 2021)
This study aims to reveal how the lifestyle of the students after carrying out activities on Instagram social media. This study uses a descriptive approach with quantitative research methods. This method provides an overview of how the influence of Instagram social media on the lifestyle of the students of. The quantitative descriptive research method instrument that the researcher uses is a questionnaire (questionnaire). This study seeks information about the impact of Instagram on student behavior, as well as how respondents respond to Instagram which is currently booming